Geomarketing using Remote Sensing: a Study on Marketing and Planning Development Strategy at Northern Riyadh - Sallman, Zouheir; Usman, Fathoni (International Journal of Engineering and Technology, 2018)
Determination of market size is a critical factor for the success of any company or business activity. This paper presents a study to provide a clear vision using remote sensing for Geomarketing and industry purposes. In order to estimate market size in the study area based on spatial data, Satellite images, Spot 6, with a 1.5 m resolution, will be used with two different dates during the year 2016. It is used to determine the growth in the housing sector with building types and construction levels in the micro-geographic area of Northern Riyadh. It is also used to identify the expected need for products of each district and the approximate time required for installation. By using remote sensing data for Geomarketing, strategies for marketing, planning and housing development could be setup.